Role of Education in Mobilising Youth to Stop Climate Change - Singh, Kavita (JOURNAL OF INDIAN EDUCATION, 2021)
Education may be considered to play an integral part in providing solution to the global problem of Climate Change, which is the biggest challenge of the twenty-first century. Education is an essential element of the global response to climate change. It helps young people understand and address the impact of global warming, encourage changes in their attitudes and behaviour and helps them adapt to climate change related trends. UNESCO has made an attempt to make climate change education an essential part of global response to climate change through its Climate Change Education for Sustainable Development programme. This programme has an objective to make people understand the implications of global warming and also increase “climate literacy” among youth. It does this by fortifying the capacity of its Member States to give quality climate change education; encouraging innovative teaching methods to incorporate climate change education in school and by bringing issues to light about climate change as well as improving non-formal education programmes through media, networking and partnerships. This paper makes an attempt to discuss the phenomenon of climate change and to what extent the youth is aware about the nuances of climate change mitigation and adaptation. Further, the author has conducted a short survey by adopting questionnaire method to analyse the response of youth towards dealing with climate crisis and how the educational institutions need to emphasise more upon the importance of climate change education.